Patterns in the provision of feed resources for stall-fed ruminant livestock in the Nepal Himalaya - Thorne, Peter J.; Tanner, J.C.; Gurung, H.B. (British Society of Animal Science, 1998)
A key characteristic of the provision of feed resources under staff feeding conditions in many smallholder systems is a high degree of variability in the types and quantities of feeds used. Striking seasonal patterns have been widely observed (e.g. Gatenby et al, 1989). However, their consequences for the supply of nutrients and differences in the extent to which individual farmers are able to minimise the impact of a fluctuating feed supply have received little attention. The issue of shorter term variation, and its likely effects on nutrient utilisation has not to our knowledge, been addressed. This paper describes some aspects of the variability in feed and nutrient supplies to stalled livestock in a mixed farming system. The likely implications for research aimed at developing improved feeding strategies and their extension are discussed.